2009
DOI: 10.4049/jimmunol.0804241
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Binding Predicts the Effects of Sequence Changes in a Human Monoclonal Antiphospholipid Antibody on Its In Vivo Biologic Actions

Abstract: The mechanisms by which antiphospholipid Abs (aPL) cause thrombosis are not fully understood. It is clear that binding to a number of phospholipid-associated Ags is important but it is difficult to identify which Ag-binding properties are most closely linked to the ability to cause biologic effects such as promotion of thrombosis and activation of endothelial cells. We have previously used an in vitro expression system to produce a panel of human monoclonal IgG molecules between which we engineered small diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 44 publications
(46 reference statements)
1
29
0
Order By: Relevance
“…Intra-peritoneal injection of these IgG into mice subjected to a femoral vein pinch stimulus showed that only those IgG (native IS4 and IS4VHi&ii/B3VL) with strong binding to thrombin promoted in vivo venous thrombosis and leukocyte adherence compared with control IgG. 17 In contrast, recombinant IS4VH/B3VL (which differs from IS4VHi&ii/B3VL by only two Arg to Ser mutations) which displayed strong CL and moderate b 2 GPI binding with negligible binding to thrombin, did not significantly increase thrombus size in treated mice compared with control human IgG. Therefore, we found that it was selectivity and not just strength of binding to CL that determined the ability of these monoclonal aPL to enhance thrombus formation in this animal model.…”
Section: Studies Into Mechanisms Of Aps Pathogenesis Utilizing Monoclmentioning
confidence: 98%
“…Intra-peritoneal injection of these IgG into mice subjected to a femoral vein pinch stimulus showed that only those IgG (native IS4 and IS4VHi&ii/B3VL) with strong binding to thrombin promoted in vivo venous thrombosis and leukocyte adherence compared with control IgG. 17 In contrast, recombinant IS4VH/B3VL (which differs from IS4VHi&ii/B3VL by only two Arg to Ser mutations) which displayed strong CL and moderate b 2 GPI binding with negligible binding to thrombin, did not significantly increase thrombus size in treated mice compared with control human IgG. Therefore, we found that it was selectivity and not just strength of binding to CL that determined the ability of these monoclonal aPL to enhance thrombus formation in this animal model.…”
Section: Studies Into Mechanisms Of Aps Pathogenesis Utilizing Monoclmentioning
confidence: 98%
“…Chukwuocha et al (2002) emphasized the importance of the H chain in autoantigen binding and functional activity in APS. On the contrary, Giles et al (2009) reported that changes in both the V H and V L region are important in determining the functional and pathogenic properties of aPL. The data presented here show that the substitution of only one amino acid in the CDR1 and CDR3 as well as 4 amino acids in the CDR2 in the V L region are sufficient to facilitate the binding to ␤2GPI.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous work focused on the binding of these variants to a range of antigens (Giles et al, 2003, 2006, 2009), effects on cultured endothelial cells in vitro , and the ability to promote thrombosis in a mouse model in vivo (Giles et al, 2009). We do not reproduce those published results in this paper, but the known sequence and key binding properties of the variants are summarised here in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…We found that altering certain arginine residues in IS4V H and/or exchanging the paired V L had dramatic effects on binding to different antigens including various PL, β 2 GPI and thrombin (Giles et al, 2003, 2005, 2006, 2009). Two such V H /V L combinations were thrombogenic in mice (Giles et al, 2009) and this pathogenicity most closely correlated with binding to thrombin rather than cardiolipin (CL) or β 2 GPI. In this study we report binding of these pathogenic and non-pathogenic V H /V L combinations to n-DI and mutated DI.…”
Section: Introductionmentioning
confidence: 99%